An assessment of the community mortgage programs of the social housing finance corporation - Marife M. Ballesteros; Tatum Ramos; Jasmine Magtibay (Philippine Institute for Development Studies (PIDS), 2015)
The Community Mortgage Program (CMP) is a financing scheme that enables organized residents of slums to borrow for land purchase and housing development. It is already considered to be the most innovative and responsive government housing program in the Philippines. Nevertheless, the CMP has yet a number of weaknesses that have not been given much attention in the years of program implementation. These issues pertain to program targeting, service delivery and organization. This study aims to review the current processes and overall performance of CMP including its variants - the localized CMP and the High Density Housing Program (HDHF). It also provides recommendations on how the identified problems can be addressed.
Keywords: 330; housing; informal settlers; community loan mortgage